Assessing the Parental Knowledge and Practices Related to Foreign Body Aspiration in Children in Majmmah, Saudi Arabia: A Cross‐Sectional Study - Ahoud Ali Al‐Shammary; Amal Kharallah Almutairi; Saja Abdullah Alharbi; Nora Mohammed Alturki; Abdulaziz Ibrahim R. Altammami; Raghad Abdullah Aloraini; Albatool Falah Aljofan; Hani Alanazi; Hamza A. Orfali (Health Science Reports)
ABSTRACT Background and Aims Foreign body aspiration (FBA) is common in the pediatric population, typically between 6 months and 4 years. It can be life‐threatening and cause complications such as obstructive bronchitis, recurrent bronchopneumonia, emphysema, and atelectasis. Public awareness and education about risk factors and behaviors to reduce the risk of FBA have been identified as one of the most crucial approaches to prevent the problem or minimize its effects. Methods A study in Majmaah, Saudi Arabia, aimed to evaluate parental practices and awareness about their children's FBA. The study included 462 parents, both Saudi and non‐Saudi, aged 18 and above. The data were collected through an electronic questionnaire in Arabic and English, and analyzed using SPSS software. The study aimed to provide insight into local parents' attitudes and actions toward their children's aspirations. Results A total of 462 parents participated in this study questionnaire, with 367 (79.44%) being mothers and 95 (20.56%) fathers of children. The majority of mothers (67.3%) and fathers (56.8%) indicated that children aged 1–5 years were more prone to swallowing or inhaling foreign objects, while a smaller percentage of mothers (21.8%) and fathers (23.2%) reported this risk for children under 1 year. The Internet emerged as the primary source of information on FBA, with 21% of parents relying on it. However, the findings revealed that (20%) of parents exhibited low levels of knowledge and practices related to FBA. Conclusion The research revealed significant associations between demographic factors and ignorance, including sex and peanut feeding. Educational level changed the way individuals considered the presence of foreign bodies in the airway system and enhanced knowledge of what to do during an emergency as well as confidence in grown‐ups' ability to handle such situations.